Pengaruh Model PBL Berbantuan PhET Simulation Terhadap Hasil Belajar Peserta Didik Kelas VIII di MTsN 6 Kota Padang - Neha Grasia; Khairil Arif; Febri Yanto (Pendidikan IPA, FMIPA, UNP, 2026)
This study aims to examine the effect of the implementation of Problem-Based Learning (PBL) assisted by PhET simulation on the learning outcomes of eighth-grade students at MTsN 6 Padang. A quasi-experimental design was used, involving an experimental group receiving PBL treatment and a control group following conventional learning methods. Data were collected through observation sheets and objective tests aligned with learning indicators on the topic of vibration, waves, and sound. The results showed that the experimental class achieved a significantly higher average posttest score (84) compared to the control class (70). The independent sample t-test analysis yielded a sig (2-tailed) of 0.000, less than the 0.05 significance level, leading to the rejection of the null hypothesis (H0). These findings indicate that PBL supported by PhET simulation significantly improves student learning outcomes. In addition, it increases student engagement and motivation in the learning process compared to traditional methods. This study concludes that the implementation of PBL with PhET simulation is an effective strategy to improve conceptual understanding and academic performance in physics education.